Comprehensive Study of a Handheld Raman Spectrometer for the Analysis of Counterfeits of Solid-Dosage Form Medicines - Klara Dégardin; Aurélie Guillemain; Yves Roggo (Journal of Spectroscopy)
The fight against medicine counterfeiting is a current focus of the pharmaceutical world. Reliable analytical tools are needed to pursue the counterfeiters. Handheld devices present the advantage of providing quick results, with analyses possibly performed on the field. A large number of solid-dosage form medicines have been analyzed with a handheld Raman spectrometer. 33 out of 39 product families could be successfully analysed. The methods were validated with 100% of correct identification. Each product was additionally tested by the methods of the other products and successfully rejected. A second validation was performed using counterfeits, placebos, and generics. All the counterfeits were rejected, with p values close to zero. Some generics presented a similar formulation to the brand products and were then identified as such. One placebo was positively identified, showing that low dosage products are difficult to analyze with Raman. Robustness tests were carried out, showing, for instance, that the operator has no influence on the results and that the analyses might be performed through transparent packaging. The discovery mode was also investigated, which proposes the chemical composition of the samples. The results demonstrated that the Raman handheld device is a reliable tool for the field analysis of counterfeits.